(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The production 18F-FDG for positron emission tomography (PET) has consistently increased over the past two decades. The risk of internal contamination at 18F-FDG production facilities exists. A setup for evaluation of the 18F-FDG activity incorporated into the OEW brain, called Head Counting System (HCS), was presented in previous works. In this study, the whole body counter setup (WBC) was evaluated for monitoring 18F incorporations. The Monte Carlo Virtual Software (VMC in-vivo) and the MCNPx code were used to assess the system calibration coefficient (CC). Three 18F distributions were simulated: i) uniformly distributed in soft tissue (UDST); ii) Na18F biodistribution (NAFB); and iii) 18F-FDG biodistribution (FDGB). The calibration coefficient of WBC was compared to the current head counting system CC under the same biodistribution conditions. The ICRP male reference voxelized phantoms (RCP_AM) was used in the simulations. The results showed that the WBC setup was more efficient than the head counter for all the studied 18F distributions: UDST = 1060 %, FDGB = 488 % and NAFB = 340 %. Despite this, especially for 18F-FDG, the possibility of bladder voiding before measurement can lead to considerable uncertainties when the WBC setup is used. On the other hand, bladder activity does not show great influence the calibration coefficient of the head counting system. Future work will evaluate the WBC sources of uncertainties in the measurement of 18F incorporated activity.